Human rights abuses at the Rio 2016 Olympics: activism and the media. Issue 1 (2nd January 2018) - Talbot, Adam; Carter, Thomas F.
Abstract: This article examines activists' use of human rights as a discourse to contest the impacts of the Rio 2016 Olympic Games by drawing on a wider ethnographic project examining activism at Rio 2016. Focusing on two areas of contention, forced evictions and police brutality, the article considers the way activists framed their grievances and how mainstream international media outlets reported those grievances. While activists fighting against forced evictions explicitly used the language of rights in their activism, media accounts tended not to discuss these issues using this lexicon. Conversely, grassroots activists protesting around the issue of police brutality did not tend to frame their grievances in terms of rights, but these issues were discussed as human rights abuses in the media. This points to a dual role played by activists fighting forced evictions: while they are fighting to keep their own homes, they are also part of a wider discursive battle for the right to housing to be recognised and respected.